Afualizando a educação em ciências : educação escolar ribeirinha intercultural na Amazônia Marajoara - Ferreira, Leliane da Costa (2023)
This dissertation aims to investigate if and how the riverside realities, knowledge and identities are inserted in the proposal of Science Education developed, in 2022, in a public school in Pará that serves riverside students in the municipality of Afuá. This is a case study conducted in a school in the municipality of Afuá, in the Marajoara Amazon, Pará State, which serves riverside students. It was carried out through Documentary Analysis (Cellard, 2012) and collection of information with the direction, the coordination and the teacher of the Science areas of the school. The Political Pedagogical Project of the institution, the proposal of Science teaching present in the state curriculum were analyzed, through the Curricular Document of the State of Pará and the Guidance Notebook of the Area of Nature Science. The study brings as focus the discussions about the realities, knowledge, curriculum, culture and identity and the intercultural perspectives with a focus on the dialogue with riverine knowledge in Science Education, inspired, above all, by Almeida, M. (2010) and Freire (1987). The results indicate that the challenges related to the context of elaboration of the PPP made its collective construction unfeasible and brought, as a consequence, the silencing of the specificities of the riverine students. It was observed in the state curriculum document a greater emphasis on the cultural diversity of the state of Pará and new perspectives for a less homogenizing curriculum. From the possibilities of insertion of riverside realities, knowledge, and identities, we announce intercultural dialogues, we are inspired by the cultural and resistance actions promoted by the teacher and artist Rose Show, who has valued and recognized the riverside teachers and the contributions of their knowledge to the Municipality of Afuá, and in the researches of Malheiros (2018) and Malheiros and Lopes (2023), Corrêa and Brito (2020), Melo (2016), and Santana (2021), which announce the perspective of the dialogue of knowledges in Science Education, allowing us to consider afualizing Science education starting from the dialogue between scientific and riverine knowledges. It is rowing in these rivers that we find new possibilities and we hope that the discussions presented here contribute to think an education for riverside schools, not only in the Afuaense context, which considers the forms of knowledge resulting from the experiences with rivers and floodplain forests, in the ideals and educacional purposes.